Hannah Arendt : Leben, Werk und Zeit - Young-Bruehl, Elisabeth 1946-2011 (S. Fischer, 1986)
Elisabeth Young-Bruehl: "Hannah Arendt. Leben und Werk." Aus dem Amerikanischen von Hans Günter Holl. S. Fischer Verlag, Frankfurt/M. 1986. 743 S., geb., 78,- DM